Pendampingan Literasi pada Komunitas Dalwamenulis# Pondok Pesantren Darullughah Wadda’wah - Rahmatullah, Asep; Hamzah, Akhmad Fauzi (Al Mu'azarah: Jurnal Pengabdian Kepada Masyarakat, 2023)
Literacy assistance to the Dalwamenulis# community, Darullughah Wadda'wah Islamic boarding school is intended so that the Islamic boarding school community can continue to provide a positive effect as part of social control. This study uses community development by carrying out several series of stages, including: preparation stage, introduction stage, implementation stage, and evaluation stage.